VD_FINDINFO Jug / 2015 / 257 vom 17. Februar 2015 - VD Tribunal cantonal (2015)
FRAIS JUDICIAIRES, INDEMNITÉ ÉQUITABLE | 3 al. 2 CPP (CH), 339 al. 3 CPP (CH), 406 al. 1 let. d CPP (CH), 426 al. 2 CPP (CH)